Does participation of rural women in agriculture associated with sociodemographic characteristics? case of Ranau District in Malaysia - Yee, Siaw Shin; Man, Norsida (Human Resource Management Academic Research Society, 2023)
Rural women play a pivotal role in the agricultural sector to feed the world. However, rural women are usually perceived by others as "helpers" to their husbands, have low participation in the workforce, and are associated with poverty. The high illiteracy rate among rural women also limits their involvement in decision-making, even if they actively engage in home and farm activities. Thus, this study investigates the association between rural women's demographic profiles and their perception levels towards their participation in agriculture activities. A cross-sectional study was conducted using a self-administered questionnaire with a sample of 248 rural women from Kundasang, selected through a simple random sampling technique. Descriptive and chi-square analyses were employed to analyse the data. Findings revealed Kadazan-Dusun as most respondents, aged between 45 and 55 years old, married, and primarily engaged in farming. Most had 1 to 10 years of agricultural experience with no agricultural education background and earned a monthly income of RM 501 to RM 1,000. The study also revealed that age and education status significantly affect the respondents' perception level towards their participation in agriculture activities. The study recommended that government should encourage and assist rural women farmers in terms of necessary farm input and incentives and provide credit facilities through various women's groups or cooperatives to enable them to participate fully and effectively in agricultural activities.